2018
DOI: 10.1080/10496491.2018.1536618
|View full text |Cite
|
Sign up to set email alerts
|

The Meaning and Effectiveness of Billboard Advertising in Least Developed Countries: The Case of Ethiopia

Abstract: This article explores media preferences of advertisers in Least Developed Countries (LDCs) using the case of Ethiopia. Study 1 demonstrates that billboards are the most popular medium in an LDC. Study 2 builds on these findings and provides an explanation of why billboards are prevalent in an LDC. The most important reasons for using billboards include tangible response, media efficiency, location, visibility, and LDC-specific factors. Study 2 also provides an overview of managers' beliefs regarding billboard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 48 publications
0
3
0
1
Order By: Relevance
“…This interest has grown steadily over the years. Gebreselassie et al (2019) mentioned that colour is essential in increasing the recognition of outdoor advertising. If that colour is a corporate colour, consumers may think of that advertised company brand when they see it outside advertisements because corporate colours symbolise the product's image.…”
Section: Entrepreneurship and Sustainability Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…This interest has grown steadily over the years. Gebreselassie et al (2019) mentioned that colour is essential in increasing the recognition of outdoor advertising. If that colour is a corporate colour, consumers may think of that advertised company brand when they see it outside advertisements because corporate colours symbolise the product's image.…”
Section: Entrepreneurship and Sustainability Issuesmentioning
confidence: 99%
“…The study's main results revealed that when the surface size of visual and text elements of outdoor advertising is equal, text elements attract more visual attention than visual elements, and advertisements with many elements attract more visual attention than those with a small number of elements. Gebreselassie et al (2019) mentioned that colour is essential in increasing the recognition of outdoor advertising. If that colour is a corporate colour, consumers may think of that advertised company brand when they see it outside advertisements because corporate colours symbolise the product's image.…”
Section: Entrepreneurship and Sustainability Issuesmentioning
confidence: 99%
“…In a likewise manner, that awareness images are catchy, they too argue that awareness images enhance the visibility of whatever it is meant for so that more people can see it and be able to make sense of it. Gebreselassie and Bougie (2019) considered Ethiopia in their research looking at the media preferences of general public, they posited that visual resources, particularly billboards, serve as the most effective communication medium between producers and consumers. They also added that they are cost-effective and easily assessable.…”
Section: Ensuring Public Awareness: Visual Illustrations In Covid-19 ...mentioning
confidence: 99%
“…Studi tentang baliho pernah dilakukan oleh Tajuddin & Zulkepli (2019) dengan memeriksa elemen tektual dan visual billboard melalui analisis semiotik bahwa billboard tidak hanya mengkomunikasikan pesan yang mendukung sosial, tetapi juga mencerminkan bahasa, identitas sosial dan nilai-nilai multikultural masyarakat. Gebreselassie & Bougie (2018) menyampaikan bahwa faktor yang berkontribusi terhadap efektivitas papan iklan adalah kejelasan, identifikasi nama, lokasi papan iklan, visual, keterbacaan, informasi, aspek fisik, kreativitas dan komunikasi pemasaran terpadu. Penelitian ini juga memberikan manfaat secara langsung yang mempengaruhi niat untuk berinteraksi dan sikap pribadi (Jere & Dutuma, 2018).…”
Section: Konteks Baliho Sebagai Media: Budaya Jawa Dan Asingunclassified